APPLICATIONS OF RAPD AND ISSR MARKERS IN PLANT GENOME ANALYSIS - Bhagyawant, Sameer S. (Innovare Journal of Agricultural Sciences, 2013)
Abstract Plant genome analysis requires a good genetic marker for tagging the gene of interest. PCR–based markers are the preferred techniques available due to their obvious advantages over conventional phenotypic markers. Random amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) are ideal genetic markers employed for various studies, mostly in studies on genetic diversity, phylogeny, gene tagging, genome mapping and evolutionary biology. These markers are simple and no sequence knowledge is required. This review reports the usefulness of RAPD and ISSR markers for the assessment of genetic diversity and its application in plant genetics in a wide range of crop plants.